I21 Self-reported physical activity, health-related quality of life and life satisfaction in huntington's disease. (13th September 2016) - Fossmo, Hanne Ludt; Walsem, Marleen Van; Frich, Jan
Abstract : Background: Research suggests that physical activity is associated with improved quality of life and motor function in individuals affected by Huntington's disease (HD). Few studies have assessed the level of physical activity in the general population of people with HD. Aims: This study aimed to describe the self-reported levels of physical activity in individuals with early to mid-stage HD, and to investigate how physical activity is associated with health-related quality of life (HRQoL) and life satisfaction (LS). Methods: 42 patients in stages I-III living in South-East Norway were included in a cross-sectional study. Physical activity, including sedentary behaviour were recorded using the short form of the International Physical Activity Questionnaire (IPAQ-SF). We assessed HRQoL using the EQ-5D Visual Analogue Scale and LS using the Satisfaction with life scale (SWLS). Socio-demographic and clinical characteristics were also collected. Descriptive and multivariate analyses were performed. Results: 6 (14%) participants reported high, 21 (50%) medium and 15 (36%) low levels of physical activity. Multivariate regression analyses revealed that physical activity levels (β value = 5.2, p = 0.047) and apathy (β value = −6.5, p = 0.003) were strongest associated with LS and sedentary behaviour (β value = −2.7, p = 0.030), depression (β value = −12.8, p = 0.042) and apathy (β value = −17.5, p = 0.008) were strongest associated with HRQoL. Conclusions: Physical activity and apathy may impact HRQoL and life satisfaction in individuals with HD. Sedentary behaviour seems to be an important variable on its own, and should be subject for further research.